(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to explore the role of green education in developing professional accountant competencies in light of the sustainability reporting requirements issued by the International Sustainability Standards Board (ISSB), particularly IFRS S1, which sets out general requirements for sustainability-related financial disclosures, and IFRS S2, which focuses on climate-related disclosures. The study is grounded in a key problem: traditional accounting education programs remain insufficient in equipping accountants with the competencies required to address increasing environmental and climate-related sustainability demands. The study adopts a descriptive–analytical and critical approach through a systematic literature review of peer-reviewed studies indexed in Scopus and Web of Science during the period 2015–2024. The findings indicate that green education contributes to the development of three main categories of professional competencies: technical sustainability knowledge, analytical and disclosure skills, and professional values and environmental attitudes. Furthermore, the results show that integrating specialized educational content in carbon accounting, sustainability reporting, and ESG data management enhances accountants’ ability to comply with IFRS S1 and IFRS S2 requirements. The study concludes by presenting a conceptual model that explains the relationship between green education and the development of professional accounting competencies, along with practical recommendations aimed at reforming accounting education curricula in Arab and developing contexts in line with modern sustainability requirements.